Does a break from sitting change biomechanical outcome measures or transient pain? A laboratory-based experimental study. - De Carvalho, Diana; Callaghan, Jack P. (Work, 2023)
BACKGROUND: Sitting can induce transient low back pain (LBP) in healthy individuals. A rest from sitting should provide relief, however, the parameters of breaks (activity type, intensity, duration, and timing) are not currently known. OBJECTIVE: The purpose of this study was to examine the effect of 2-minute walking breaks at 40-minute intervals on sitting-induced LBP. METHODS: Thirty-two healthy participants were recruited for a within-control study: two randomly presented sessions of sitting for 2 hours with and without breaks. Outcome measures were compared between condition and pain group using a three-way ANOVA with significance atp > 0.05. RESULTS: Walking breaks at 40-minute intervals result in significantly lower pain ratings than those taken immediately before the break for sitting-induced back pain developers. However, this relief is short lived (<10 minutes), with ratings increasing to pre-break levels once the sitting exposure resumes. There were no differences in biomechanical factors between sessions. Regardless of session type, pain developers displayed higher spine fidget frequency than non-pain developers, females sat with less spine flexion, with greater gluteal activation levels, and with their center of pressure approximately half a centimeter to the left and forward compared to males, and males had significantly greater peak pressures over a smaller area compared to females. CONCLUSION: Walking breaks at 40-minute intervals provide significant, but temporary, relief of sitting-induced back pain for pain developers. Future work should optimize break parameters and examine the longer-term benefit of breaks, especially for individuals that are not able to tolerate sitting for extended durations.